Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1952
DOI: 10.1002/jlac.19525770108
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über Acetylene VI: Die Reaktion der Acetylene mit Persäuren. Acetylenoxyde

Abstract: Die Acetylene erweisen sich in einigen Fallen, z. B. gegenuber katalytisch erregtem Wasserstoff, als reaktionsfahiger als die entsprechenden Athylene. Denn es ist moglich, auch mit vergifteten Katalysatoren die ersteren zu hydrieren, denen gegeniiber die letzteren sich refraktar verhalten. Umgekehrt finden sich in der Literatur zahlreiche Beispiele dafiir, daB Halogene an Plefine wesentlich leichter angelagert werden als an Acetylene. So wird im All$-acetylen Brom zuniichst an die Doppelbi~dung addiertz) :Ein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1957
1957
1983
1983

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This compound, however, should certainly not be isolable under normal conditions, and the reaction of alkynes with strong oxidants is known to give other products. 23 The next claim of a successful oxirene synthesis8 involved a nonoxidative approach (IIID1), but in 1952 Shubach and Franzen9 claimed the oxidation of 5-decyne (9) to dibutyloxirene (10) with peroxyethanoic acid24 (Scheme II). However, Franzen soon showed that the product of the oxidation was in Scheme III fact 6-decen-5-one (11) (Scheme II), and went on to show that the oxidation of alkynes with peroxyethanoic acid can produce, besides a,/3-unsaturated ketones, products plausibly derivable from them (eq 3)25 or from ketenes (eq 4).…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…This compound, however, should certainly not be isolable under normal conditions, and the reaction of alkynes with strong oxidants is known to give other products. 23 The next claim of a successful oxirene synthesis8 involved a nonoxidative approach (IIID1), but in 1952 Shubach and Franzen9 claimed the oxidation of 5-decyne (9) to dibutyloxirene (10) with peroxyethanoic acid24 (Scheme II). However, Franzen soon showed that the product of the oxidation was in Scheme III fact 6-decen-5-one (11) (Scheme II), and went on to show that the oxidation of alkynes with peroxyethanoic acid can produce, besides a,/3-unsaturated ketones, products plausibly derivable from them (eq 3)25 or from ketenes (eq 4).…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…Epoxidation of acetylenes to produce oxirenes initially is not only slower but was also found by Schlubach and Franzen (16) to result in cleavage of the triple bond to acids of shorter chain length. Because of this difference in reactivity, peroxyacetic acid may be employed for selective epoxidation of an olefin bond that is conjugated with a triple_bond.…”
mentioning
confidence: 66%
“…Oxirenes, potential 4tt antiaromatic systems,1 have been frequently proposed as transient intermediates in the peroxyacid oxidation of acetylenes. [2][3][4][5][6][7] The results of the earlier product2-6 and kinetic studies7 are consistent with but do not uniquely require the oxirene mechanism. Recent evidence seems to favor a pathway featuring ketocarbenes as reactive intermediates.8 We now present evidence which, for the first time, compellingly implicates oxirenes as the first-formed intermediates in the peroxidation of acetylenes.…”
mentioning
confidence: 81%